1986
DOI: 10.1159/000173988
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Serum Enzyme Activity in Acute Myocardial Infarction and Morbidity during a 2-Year Follow-Up

Abstract: In 585 patients with a first myocardial infarction the enzymatically estimated infarct size was related to the clinical course during a 2-year follow-up. Infarct size was estimated from maximum heat-stable lactate dehydrogenase activity. A higher maximum serum activity was associated with a higher mortality rate, more treatment with diuretics, digitalis and antiarrhythmics and a lower frequency of return to work. Patients with smaller infarcts according to maximum serum activity, however, had a higher incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
1988
1988

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 11 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…It has been shown that early intervention with streptoki nase [1,2] and with beta-blockers [3,4] can reduce the early mortality and regarding beta-blockade several morbidity aspects in the early phase appear to be favorably af fected. The relationship between the original infarct size and long-term morbidity, how ever, appears to be more complex [5] and not much is known whether limitation of the infarct size can improve morbidity and qual ity of life in a longer perspective. In this paper we report on morbidity and quality of life during a 5-year follow-up after early in tervention with metoprolol in patients with suspected acute myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that early intervention with streptoki nase [1,2] and with beta-blockers [3,4] can reduce the early mortality and regarding beta-blockade several morbidity aspects in the early phase appear to be favorably af fected. The relationship between the original infarct size and long-term morbidity, how ever, appears to be more complex [5] and not much is known whether limitation of the infarct size can improve morbidity and qual ity of life in a longer perspective. In this paper we report on morbidity and quality of life during a 5-year follow-up after early in tervention with metoprolol in patients with suspected acute myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%